Pembangkit Listrik Tenaga Surya dengan Pengisian Daya Otomatis Menggunakan Sistem PWM Berbasis Mikrokontroler - Widodo, Sulistyo; Wahyuningsih, Erfiana; Adhiyoga, Yohanes Galih (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Indonesia will become a net importer if it runs out of oil and gas reserves within the next 11 to 12 years if no alternative energy sources are developed. Therefore, there is a need to utilize alternative energy that is not dependent on oil or gas. One alternative energy is using solar light energy. This research designed a device that can convert the energy of sunlight into electrical energy and automatically store electrical energy in a battery with PWM (Pulse Width Modulation) so that it can be used as alternative energy, and help reduce the consumption of electricity from PLN. The battery used 12V 80Ah and a solar panel module 50W for energy storage and system resources. The research results show that systems can automatically charge energy using sunlight and turn the lights to 7W. Using the charging system automatically uses PWM to reduce the risk of damage to the battery because, in the charging process, battery conditions will be monitored. The maximum power generated from solar panel modules used is 35.57 W.